2013
DOI: 10.1177/0194599813516733
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic Variability of Laryngeal Premalignant Lesions: Histological Evaluation and Carcinoma Transformation

Abstract: Severe dysplasia shows the same carcinoma transformation potential as the carcinoma in situ does. Clinically, more attention to severe dysplasia is needed in comparison with mild and moderate dysplasia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 25 publications
0
10
0
Order By: Relevance
“…A total of 18 articles with 3243 participants were included in the final systematic review, and all of these were included in the meta-analysis. [19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36] Study characteristics are shown in Table 1.…”
Section: Study Selection and Characteristicsmentioning
confidence: 99%
See 3 more Smart Citations
“…A total of 18 articles with 3243 participants were included in the final systematic review, and all of these were included in the meta-analysis. [19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36] Study characteristics are shown in Table 1.…”
Section: Study Selection and Characteristicsmentioning
confidence: 99%
“…A total of 17 studies were combined to assess the odds of malignant transformation of moderately dysplastic lesions com- pared with mildly dysplastic lesions, resulting in 640 cases of moderate dysplasia and 1032 cases of mild dysplasia (Figure 2A). [19][20][21][23][24][25][26][27][28][29][30][31][32][33][34][35][36] Data synthesis showed that moderately dysplastic lesions had higher odds of undergoing malignant transformation compared with mildly dysplastic lesions (OR, 2.90; 95% CI, 2.06-4.09). The I 2 statistic was 0%, which indicated a low level of heterogeneity among the studies.…”
Section: Comparison Of Malignant Potential By Dysplasia Gradementioning
confidence: 99%
See 2 more Smart Citations
“…[2][3][4] Early diagnosis of head and neck (HN) lesions is therefore essential to prevent the progression to invasive carcinoma. 5 Yet the categorization of HN dysplasias remains a contentious issue 6,7 due to the varying terminologies, grading methodologies, and low to moderate reproducibility among pathologists 6,8,9,10,11,12 (Table 1).…”
Section: Introductionmentioning
confidence: 99%